2012
DOI: 10.2147/ndt.s37174
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of facial expression in patients with obsessive-compulsive disorder and schizophrenia using the Facial Action Coding System: a preliminary study

Abstract: BackgroundResearch shows that impairment in the expression and recognition of emotion exists in multiple psychiatric disorders. The objective of the current study was to evaluate the way that patients with schizophrenia and those with obsessive-compulsive disorder experience and display emotions in relation to specific emotional stimuli using the Facial Action Coding System (FACS).MethodsThirty individuals participated in the study, comprising 10 patients with schizophrenia, 10 with obsessive-compulsive disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…The facial expression of each patient in response to the vision of the films was video recorded. These video clips, all in Italian, were watched by the three groups of subjects in the same order, according to the protocol established by Gross21 and according to the protocol of a previous study by our research team:22 video 1 = neutral; video 2 = amusement; video 3 = fear; video 4 = surprise; video 5 = anger; video 6 = sadness; video 7 = disgust; video 8 = amusement.…”
Section: Methodsmentioning
confidence: 99%
“…The facial expression of each patient in response to the vision of the films was video recorded. These video clips, all in Italian, were watched by the three groups of subjects in the same order, according to the protocol established by Gross21 and according to the protocol of a previous study by our research team:22 video 1 = neutral; video 2 = amusement; video 3 = fear; video 4 = surprise; video 5 = anger; video 6 = sadness; video 7 = disgust; video 8 = amusement.…”
Section: Methodsmentioning
confidence: 99%
“…Despite clear indications for altered emotion experience in OCD in individual contexts, less is known about the emotional reactions of individuals with OCD in response to social emotioninducing stimuli. Several studies have investigated the experience of basic emotions in patients with OCD as indexed by their facial expressions in response to emotion-inducing video clips of social scenarios (114,117,118). Mergl et al (117) showed that patients with OCD demonstrated significantly slower initial velocity of involuntary laughing movements in response to a humorous movie clip of Mr. Bean.…”
Section: Emotion Experiencementioning
confidence: 99%
“…The software Emotient from iMotions was utilized to analyze these videos. This software uses the facial action coding system (FACS), which defines specific facial units, called action units (AU) ( Figure 1), and track their alterations from a neutral baseline during movements and expressions (Bersani, Bersani, Valeriani, & Robiony, 2012;Hamma, Kohlerb, & Gurb, 2011). Emotient is able to detect the subject's face automatically by applying the Viola Jones Cascaded Classifier algorithm (Dabhi & Pancholi, 2013), used in smartphone technology, to detect 6 facial landmarks and create a sim- of a target AU being present.…”
Section: Software Based Video Analysismentioning
confidence: 99%